2021
DOI: 10.47723/kcmj.v17i2.539
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Physical Correlates of Body Image Dissatisfaction among High School Egyptian Students

Abstract: Background: Body image is one of the most important psychological factors that affects adolescents’ personality and behavior. Body image can be defined as the person’s perceptions, thoughts, and feelings about his or her body. Objectives: to identify the prevalence of body image concerns among secondary school students and its relation to different factors. Subjects and methods: A cross-sectional study conducted in which 796 secondary school students participated and body shape concerns was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 29 publications
1
4
2
Order By: Relevance
“…A study conducted in Malaysia and Nepal used the Body Shape Questionnaire to assess body image dissatisfaction, unlike this study, which used the BPS. In addition, there can also be disparity within the population, as body image dissatisfaction is determined by different socioeconomic problems, which may result in differences in prevalence (17). This study showed a slightly higher prevalence of body image dissatisfaction compared to a previous study conducted among adolescents aged between 11 and 17 years who were students in public schools in Brazil (12).…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…A study conducted in Malaysia and Nepal used the Body Shape Questionnaire to assess body image dissatisfaction, unlike this study, which used the BPS. In addition, there can also be disparity within the population, as body image dissatisfaction is determined by different socioeconomic problems, which may result in differences in prevalence (17). This study showed a slightly higher prevalence of body image dissatisfaction compared to a previous study conducted among adolescents aged between 11 and 17 years who were students in public schools in Brazil (12).…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies show different distributions of BID among adolescents at different site. In a study conducted among adolescents in Brazil, 19.5% had body image dissatisfaction (12), 60.1% in Malaysia (13), 25% among girls, and 10% among boys in Indonesia (14), 75.2% in Kathmandu in Nepal (15), 21.2% in Jordan (16) and 21.6% in Egypt (17).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations